Islands in Time : Island Sociogeography and Mediterranean Prehistory - Patton, Mark (EBL-Schweitzer, 2013)
Islands in Time explores the ecological and cultural development of prehistoric island societies. It considers the prehistory of the Mediterranean and offers an explanation of the effects of isolation on the development of human communities. Evidence is drawn from a broad range of Mediterranean islands including Cyprus, Crete and the Cyclades, Malta, Lipari, Corsica and Sardinia